Flood susceptibility mapping using GIS-based composite mapping analysis: a multi-district assessment in Lampung Province, Indonesia - Muhammmad Rizky Alfajar; Lesi Mareta; Ajeng Utari Siti Saodah (Scientific Nexus, 2025)
Flooding is a recurring hydrometeorological disaster in Lampung Province, Indonesia, particularly affecting Pesawaran Regency, South Lampung Regency, and Bandar Lampung City. This study mapped flood susceptibility using Geographic Information Systems (GIS) with Composite Mapping Analysis (CMA) and scoring methods to support disaster risk reduction planning. Six parameters were analyzed: rainfall, land cover, slope, elevation, soil type, and river buffer distance. Parameter weights were derived objectively through CMA based on spatial analysis of 258 historical flood events (2018-2024). Rainfall data (2015-2024) were interpolated using Inverse Distance Weighting, and spatial analysis was conducted in ArcGIS 10.8. Results show that 90.66% of the study area falls within moderate to high susceptibility classes. Rainfall received the highest weight (20%), followed by elevation (19%), soil type (18%), land cover (16%), river buffer (14%), and slope (13%). Model validation achieved 77.78% accuracy when compared with historical flood locations across 45 sub-districts. High susceptibility areas are characterized by annual rainfall exceeding 2,500 mm, elevations below 50 masl, poor soil infiltration capacity, and dense settlement. The CMA method provides objective parameter weighting while maintaining computational simplicity suitable for resource-constrained settings, offering a practical framework for flood susceptibility assessment in similar tropical regions.